Acute subretinal abscess in Staphylococcus aureus septicaemia with endophthalmitis showcased by multimodal retinal imaging and with 2-year follow-up. Issue 1 (28th November 2018) - Prajapati, Rita; Newton, Pippa; Ahmad, Sameena; Kelly, Simon
Abstract : A middle-aged man presented to emergency services with central vision loss in the setting of flu-like illness with fever. A striking subfoveal abscess was observed in the right fundus. Focal acute chorioretinal inflammation was noted in the asymptomatic fellow eye. Staphylococcus aureus septicaemia was subsequently diagnosed. He presented with undiagnosed HIV infection and latent syphilis. Serial high-definition multimodal retinal imaging showcased resolution of the dome-shaped subretinal abscess following treatment with intravenous flucloxacillin. A chorioretinal scar swiftly replaced the subfoveal abscess. Peripheral right vision and full left vision was retained. Vision loss due to endogenous endophthalmitis in systemic sepsis is an emergency requiring prompt multidisciplinary care. Sight and life are at risk—thus this is not a diagnosis to miss! Early recognition is paramount to health and in retaining vision. We briefly review relevant literature and portray how multimodal imaging guided response to treatment of acute subretinal abscess.